Systemic chronic inflammation in end-stage renal disease patients and possible treatment approaches - Dudar, I. (Ukrainian Journal of Nephrology and Dialysis, 2020)
Systemic chronic inflammation (SCI) is a common feature of chronic kidney disease (CKD) which is most pronounced in dialysis patients. SCI is associated with cardiovascular pathology, various comorbid conditions and high mortality risk in dialysis patients. The existing dialysis methods are ineffective for removing substances involved in SCI (medium molecular uremic toxins: cytokines, growth factors, adiponectin, hormones, and other substances). The dialysis technology development has always aimed to create the membranes that will be as close as possible to the natural glomerular membrane. Currently, Middle Cut-Off membranes have been created. The use of Middle Cut-Off membranes is implemented in a new method of dialysis therapy entitled expanded hemodialysis (HDx). Further studies will determine the expected perspective of these membranes and HDx in the treatment of dialysis patients.